Efficiency Marketing of Onion In Bantul Regency - Wulan Priantika; Suhatmini Hardyastuti; Irham Irham (HABITAT, 2021)
Onion is one of the potential horticultural plants in Yogyakarta Special Region. Onion production center is located in District Saden and Imogiri District, Bantul regency. This research has objectives to (1) know the onion marketing chain in Bantul Regency and (2) to know the most efficient marketing channel using Acharya method. Respondents were randomly selected as many as 60 onion farmers in Bantul District. Snowball method is used to get two wholesalers, three merchant collectors, and three retailers by following the distribution of onion sales from farmers to consumers. The results showed that the onion marketing chain in Bantul district consists of three marketing channels. The most abundant onion chain of marketing compositions in Bantul District is farmers-wholesalers-collectors-retailers-consumers, farmers-wholesalers-collectors, and farmers- collectors-retailers. Marketing on onion in Bantul Regency is done most efficiently in the third marketing channel that is farmers-collectors-retailers. This research is expected to give information about the marketing chain of onion in Bantul regency.